Effects of Oligosaccharides Isolated From Pinewood Hot Water Pre-hydrolyzates on Recombinant Cellulases - Fang, Hong; Kandhola, Gurshagan; Rajan, Kalavathy; Djioleu, Angele; Carrier, Danielle Julie; Hood, Kendall R.; Hood, Elizabeth E. (Frontiers in Bioengineering and Biotechnology, 2018)
Loblolly pine residues have enormous potential to be the raw material for advanced biofuel production due to extensive sources and high cellulose content. Hot water (HW) pretreatment, while being a relatively economical and clean technology for the deconstruction of lignocellulosic biomass, could also inhibit the ensuing enzymatic hydrolysis process because of the production of inhibitors. In this study, we investigated the effect of oligosaccharide fractions purified from HW pre-hydrolyzate of pinewood using centrifugal partition chromatography (CPC) on three recombinant cellulolytic enzymes (E1, CBHI and CBHII), which were expressed in the transgenic corn grain system. The efficiency of recombinant enzymes was measured using either a 4-methylumbelliferyl-β-D-cellobioside (MUC) or a cellulose-dinitrosalicylic acid (DNS) assay system. The results showed that HW pre-hydrolyzate CPC fractions contain phenolics, furans, and monomeric and oligomeric sugars. Among CPC fractions, oligomers composed of xylan, galactan and mannan were inhibitory to the three recombinant enzymes and to the commercial cellulase cocktail, reducing the enzymatic efficiency to as low as 10%.